CORI 融入社會領域教學對國民小學五年級學生閱讀成效的影響 Concept-Oriented Reading Instruction Integrated into Social Studies on the Reading Performance of Fifth-Grade Students - 陳海泓 Hai-Hon Chen (National Taiwan Normal University, 2015)
本研究旨在探討概念導向閱讀教學（Concept-Oriented Reading Instruction, CORI）融入社會領域教學對國小五年級學生閱讀動機、閱讀理解策略的運用能力與閱讀理解力的影響。採準實驗研究之不等組前、後測設計，以臺南市某國小兩班學生為對象，實驗組29 位，進行CORI教學；控制組28 位，以教科書為主的傳統教學方式。實驗教學14 節，以「閱讀動機問卷」、「閱讀理解策略運用能力評量」和「閱讀理解力測驗」作為研究工具進行前、後測。以t 考驗和單因子共變數分析進行資料處理。研究結果顯示：CORI 能提升國小五年級學生的閱讀動機、增進學生閱讀理解策略的運用能力，以及學生的閱讀理解力。根據研究結果，提出建議供社會領域教師實施CORI 教學及未來研究之參考。 This study investigated the effects of teachers' implementation of the four Concept-Oriented Reading Instruction (CORI) principles (i.e., reading motivation, reading strategy use, conceptual knowledge, and collaborative learning) in the content area of social studies on the reading motivation, reading strategy use, and reading comprehension of fifth-grade students. A quasi experimental method was adopted, and two classes of 57 fifth-grade elementary school students in Tainan city, Taiwan were used as samples. The experimental group participated in CORI, whereas the control group were instructed using a didactic teaching method. The experimental instruction intervention lasted for 14 hours. The Reading Motivation Inventory, Comprehension Strategy Use Measure, and a reading comprehension test were used as instruments for collecting data. A t test and ANCOVA were performed to analyze the data. The results indicate that CORI: (1) increases the reading motivation of students, (2) improves the reading comprehension strategy use of fifth-grade students, and (3) increases their reading comprehension. This paper provides suggestions to teachers and future researchers based on these findings.